Analisis Aspek yang Mempengaruhi Penghindaran Pajak dengan Parameter Ukuran Perusahaan, Leverage, Intensitas Modal, Komisaris Independen dan Komite Audit - Ahmad Bukhori Muslim; Dian Sulistyorini Wulandari; Erman Firmansyah (Journal of Trends Economics and Accounting Research, 2023)
Tax avoidance is all actions taxpayers take to legally reduce the tax burden. More specifically, tax evasion can be defined as an attempt to uncover loopholes in the tax law until a legal defect is found that allows tax evasion and savings on taxes to be paid. Tax avoidance can also be interpreted as an effort by taxpayers, both individuals, and entities, to minimize tax payments. The type of data used in this study is secondary data. The data source comes from the complete financial statements of mining companies with a sample of 20 companies listed on the Indonesia Stock Exchange in 2018-2021. The complete data source comes from the Indonesia Stock Exchange website www.idx.co.id. The analytical technique used is quantitative analysis with the analytical test used in this study is multiple linear regression analysis. Based on the results of hypothesis testing, firm size (0,629), leverage (0,434), independent commissioners (0,816) and audit committees (0,840) have no effect on tax avoidance, and capital intensity has a positive effect on tax avoidance.